An Atypical Case of Bartonella henselae Osteomyelitis and Hepatic Disease - Dionna M. Mathews; Katie M. Vance; Pamela M. McMahon; Catherine Boston; Michael T. Bolton (Case Reports in Pediatrics)
Bartonella henselae is a Gram-negative bacterium and the causative agent of cat scratch disease (CSD). Atypical presentations of B. henselae that involve the musculoskeletal, hepatosplenic, cardiac, or neurologic systems are rare. In this case report, we describe a case of B. henselae osteomyelitis involving bilateral iliac bones complicated by hepatic lesions in a 12-year-old immunocompetent female patient. Although B. henselae is a rare cause of osteomyelitis, it should be considered when patients who present with fever, pain, and lymphadenopathy do not respond to routine osteomyelitis therapy.